Monte Carlo Modeling of Mixed-Anisotropy [Co/Ni]2/Nife Multilayers - Altbir-Drullinsky, D; Escobar-Donoso, R; Castillo-Sepulveda, S (Institute of Electrical and Electronics Engineers Inc., 2016)
The magnetic properties of a thin film consisting of an exchange-coupled [Co/Ni]2/NiFe multilayer have been studied as a function of the NiFe thickness by using Monte Carlo modeling and compared with experimental results of [Co/Ni]4/Co/NiFe multilayers. Both modeling and experiment showed that the NiFe thickness controls the effective anisotropy. The direction of the easy axis is determined by a competition between the perpendicular crystalline anisotropy of the Co/Ni and the shape anisotropy of the multilayer. As the thickness of the NiFe layer increases, the reversal mechanism of the thin film changes from the nucleation of reverse domains to vortex propagation. Therefore, our results reveal the magnetic configurations and the easy axis reorientation of mixed-anisotropy multilayers. © 2015 IEEE.